Prevalence and Associated Factors Affecting Outcomes of Adult Patients with Cardiac Arrest Who Receive Cardiopulmonary Resuscitation in Emergency Department of a Tertiary Hospital - Pradhan, Alok; Shrestha, Roshana; Shrestha, Anmol Purna; Basnet, Samjhana; Shrestha, Sanu Krishna (Journal of College of Medical Sciences-Nepal, 2024)
Background Cardiopulmonary resuscitation (CPR) aims at restoring spontaneous circulation in a victim of cardiac arrest. This study intends to find out the demographic information of cardiac arrest patients, their outcomes and the possible factors that could affect the outcomes. Methods A hospital-based cross-sectional study was conducted at Dhulikhel Hospital to investigate cardiac arrest outcomes among patients aged over 14 years who either presented with or developed cardiac arrest in the Emergency Department. Data were documented and, then entered into Microsoft Excel and analyzed using SPSS. Descriptive statistics were used to summarize categorical and continuous variables, while a Chi-square test (p < 0.05) assessed associations between selected variables and CPR outcomes. Results The majority of patients were over 65 years old (31.9%), with the smallest group under 25 years (10.1%). Regarding gender distribution 34.8% were female. Trauma was present in 24.6% of cases, while 48.9% were witnessed by bystanders but none of them received CPR. Initial rhythm was predominantly asystole (87%). CPR lasted for 20-40 minutes in 47.8% of cases and over 40 minutes in 14.5%, averaging 24.1 minutes. 40.6% patients had ROSC after CPR while 59.4% had no Return of Spontaneous Circulation (ROSC). Statistically significant associations with CPR outcomes were found for sex, site of cardiac arrest, trauma, witnessed events, CPR duration, and intubation (p-value <0.05). Conclusions Our hospital experiences a high prevalence of cardiac arrest and has comparable ROSC rate. Statistically significant variables associated with outcomes of CPR were, sex, site of cardiac arrest, Trauma, Witnessed event, Duration of CPR and Intubation.